2018
DOI: 10.33221/jikm.v7i3.125
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Hubungan Iklim (Curah Hujan, Kelembaban, Suhu Udara dan Kecepatan Angin) dengan Kasus ISPA di DKI Jakarta Tahun 2011 – 2015

Abstract: Perubahan iklim menimbulkan efek terhadap kesehatan manusia secara langsung maupun tidak langsung,  efek langsung berupa efek ekstrim dingin dan panas. Curah hujan yang ekstrim dapat meningkatkan kasus penyakit ISPA. Kasus ISPA dari tahun ketahun meningkat berdasarkan SDKI 2007, sebesar 11.2%. Penelitian ini menggunakan studi ekologi untuk melihat hubungan iklim (curah hujan, kelembaban, suhu udara, kecepatan angin) dengan kasus ISPA di DKI Jakarta Tahun 2011 – 2015.  Populasi adalah seluruh data penderita ISP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 1 publication
(1 reference statement)
3
5
0
1
Order By: Relevance
“…Based on table 1, the results of the SPSS output using the t-test obtained t value of -4.703 which indicates that rainfall harms the incidence of Respiratory for toddlers, which means that the higher the rainfall, the lower the incidence of Respiratory in children under five. The results of this study are in line with the research conducted by Ernyasih E et al (2018). It was found that there was a significant relationship between rainfall (p = 0.013) and cases of Respiratory in Jakarta in 2011-2015 (2018) (17).…”
Section: The Influence Of Rainfall On the Incidence Of Dhf And Ari Fo...supporting
confidence: 90%
See 1 more Smart Citation
“…Based on table 1, the results of the SPSS output using the t-test obtained t value of -4.703 which indicates that rainfall harms the incidence of Respiratory for toddlers, which means that the higher the rainfall, the lower the incidence of Respiratory in children under five. The results of this study are in line with the research conducted by Ernyasih E et al (2018). It was found that there was a significant relationship between rainfall (p = 0.013) and cases of Respiratory in Jakarta in 2011-2015 (2018) (17).…”
Section: The Influence Of Rainfall On the Incidence Of Dhf And Ari Fo...supporting
confidence: 90%
“…The results of this study are in line with the research conducted by Ernyasih E et al (2018). It was found that there was a significant relationship between rainfall (p = 0.013) and cases of Respiratory in Jakarta in 2011-2015 (2018) (17). This possibility is due to extreme rainfall that can increase cases of upper respiratory tract infections (ARI) because the area becomes cold and humid.…”
Section: The Influence Of Rainfall On the Incidence Of Dhf And Ari Fo...supporting
confidence: 88%
“…Prison, Lowokwaru Malang. This is in accordance with research conducted by [12], the temperature in the room greatly affects the health of family members who inhabit it, if the temperature in the dwelling is low it can cause the growth of bacteria that cause disease to reproduce properly.…”
Section: Relationship Between Temperature and Arisupporting
confidence: 90%
“…If the humidity in the room is high, it allows the growth of bacteria to be faster too, making it easier for someone to contract diseases caused by bacteria in humid air, including ARI. (Ernyasih, Fajrini F, 2018) From the results of compliances at the time of observation, it can be seen that the lighting of each replier's house that's visited doesn't meet the conditions because The habit of the repliers who infrequently open windows and the ventilation area that doesn't meet the conditions because of the high moisture in the room, so it's necessary to intermediate with the geste of opening windows every day and perfecting ventilation that doesn't meet the conditions.…”
Section: The Association Of Humidity With the Incidence Of Ari In Toddlersmentioning
confidence: 99%